Association between the three functional miR-146a single-nucleotide polymorphisms, rs2910164, rs57095329, and rs2431697, and autoimmune disease susceptibility: A meta-analysis. (2nd October 2016) - Park, Robin; Lee, Won Jin; Ji, Jong Dae
Abstract: Studies suggest associations between the miR-146a single nucleotide polymorphisms (SNPs) and susceptibility to autoimmune diseases. However, the results are inconsistent and inconclusive. Therefore, the aim of this study was to arrive at a conclusion about the association between the three functional miR-146a SNPs and autoimmune disease risk. Studies were identified through PubMed/MEDLINE searches for studies published up to January 2016 using as keywords rs2910164, rs57095329, rs2431697, and miR-146a polymorphisms. Thirty studies were included in the meta-analysis. The SNP rs2910164 G > C was found to be associated with increased risk of multiple sclerosis (CC + CG versus GG, OR = 1.25, 95% CI: 1.01–1.55), with decreased risks of psoriasis (C versus G, OR = 0.81, 95% CI: 0.69–0.96; CC versus GC + GG, OR = 0.73, 95% CI: 0.56–0.94), Behcet's disease (CC versus GC + GG, OR = 0.60, 95% CI: 0.50–0.73), asthma (C versus G, OR = 0.80, 95% CI: 0.69–0.93; CC versus GC + GG, OR = 0.65, 95% CI: 0.48–0.86), and uveitis (CC + CG versus GG, OR = 0.61, 95% CI: 0.49–0.77). The SNP rs2431697 C > T was found to be associated with an increased risk of SLE (T versus C, OR = 1.26, 95% CI: 1.15–1.38; TC + TT versus CC, OR = 1.28, 95% CI: 1.03–1.58; TT versus TC + CC, OR = 1.40, 95% CI: 1.21–1.62). The SNP rs57095329 A > G was found to be associated with an increased risk of SLE (G versus C, OR = 1.25, 95% CI: 1.17–1.35). The miR-146a SNPs rs2910164, rs57095329, rs2431697 are associated with susceptibility to certain autoimmune diseases. However, for other autoimmune diseases, they may be protective or insignificant.